Genetic Risk, Adherence to a Healthy Lifestyle, and Coronary Disease - Khera, Amit V; Emdin, Connor A; Drake, Isabel; Natarajan, Pradeep; Bick, Alexander G; Cook, Nancy R; Chasman, Daniel I; Baber, Usman; Mehran, Roxana; Rader, Daniel J; Fuster, Valentin; Boerwinkle, Eric; et al. (The New England journal of medicine, 2016)
Using a polygenic score of DNA sequence polymorphisms, the authors of this study quantified genetic risk and assessed four healthy lifestyle factors. Among participants at high genetic risk, a healthy lifestyle was associated with a reduced risk of coronary disease. Both genetic and lifestyle factors are key drivers of coronary artery disease, a complex disorder that is the leading cause of death worldwide. 1 A familial pattern in the risk of coronary artery disease was first described in 1938 and was subsequently confirmed in large studies involving twins and prospective cohorts. 2 – 6 Since 2007, genomewide association analyses have identified more than 50 independent loci associated with the risk of coronary artery disease. 7 – 15 These risk alleles, when aggregated into a polygenic risk score, are predictive of incident coronary events and provide a continuous and quantitative measure of genetic susceptibility. 16 – 24 Much . . .